Q: What is 3a plus 5b plus 7a?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3a - 2b

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

-7a + 3a = -4a

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.

It is an expression that can be simplified to: 3a-2b+c

Related questions

3a - 2b

3a - 2b

10a+7b undefined variables cannot be determined

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

-7a + 3a = -4a

What is the solution of -2a plus 3a plus 5b

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.

3a + 5b - 6a - 9b = -3a - 4b

It is an expression that can be simplified to: 3a-2b+c

4a + 3a = (4 + 3)a = 7a

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

24am - 9an + 40bm - 15bn = 3a*(8m - 3n) + 5b*(8m - 3n) = (3a + 5b)*(8m - 3n)